Halal risk assessment in broiler hatchery operations - Ramli, Mohd Hasli; Ajmain @ Jima’ain, Muhammad Talhah; Rosman, Arieff Salleh; Md Sikin, Adi; Jamaludin, Mohammad Aizat (Human Resource Management Academic Research Society, 2023)
Halal risk assessment in the poultry industry mainly focuses on identifying halal risks at slaughtering and chicken meat processing. Yet halal risk at the early stage of broiler supply before being transferred to livestock farms has not been discussed intensely. This study explores an overview of egg-hatching activities in proposing the halal critical points (HCP) involved in hatchery operation. It was found that five activities in the hatching process had been identified as significant points of halal risk, which are egg receiving from breeder farms, egg incubation, chick disposal, vaccination of chicks, and logistics. A qualitative approach was used to gather information via document analysis and a semi-structured interview in describing and analyzing the halal hazards and risks associated in hatchery operations. The study emphasized that halal risk assessment could be carried out in the commercial broiler hatchery operation of other fowl, such as ducks or quail. Besides, give a positive impact on maintaining the halal integrity of meat sources to Muslim consumers.